Bimolecular-induced hierarchical nanoporous LiTi2(PO4)3/C with superior high-rate and cycling performance. Issue 62 (19th July 2017) - Sun, Wenwei; Liu, Jiehua; Liu, Xiaoqian; Fan, Xiaojing; Zhou, Kuan; Wei, Xiangfeng
Abstract : Carbon-coated hierarchical LiTi2 (PO4 )3 was synthesized by a facile bimolecular (glucose and DMEA) assisted hydrothermal reaction and a solid-state reaction, and exhibits excellent high-rate and cycling performance. Abstract : We employed a facile bimolecular (glucose and DMEA) assisted hydrothermal reaction and a solid-state reaction to obtain carbon-coated hierarchical LiTi2 (PO4 )3 on a large scale. The nanoporous material exhibits excellent high-rate and cycling performance owing to enhanced electronic conductivity from the ultrathin carbon layer, Ti 3+ and the shortened path for Li + diffusion by nanoporous frameworks.